Resistance-Associated Substitutions (RAS) and Clinical Factors as Determinants of Sofosbuvir-Daclatasvir Treatment Outcomes in Chronic Hepatitis C Patients - Kurniawan, Juferdy; Handayu, Anugrah Dwi; Aprilicia, Gita; Bahri, Darlene Raudhatul; Hasan, Irsan (Acta Medica Indonesiana, 2025)
Background: Direct acting antivirals (DAAs) have demonstrated remarkable efficacy, in achieving hepatitis C viral (HCV) elimination rates higher than 90%. One particular concern associated with treatment failure is the emergence of resistance associated substitutions (RASs) in the genome. The occurrence of RASs highlights the adaptability and resilience of the HCV. This highlights the importance of RASs mutation, enabling the development of new therapeutic strategies to combat these resistant strains. This study aims to determine the presence of early HCV mutations in chronic hepatitis C in Indonesia and the association between this mutation to the efficacy of sofosbuvir-daclatasvir. Methods: We conducted a prospective longitudinal study in naïve hepatitis C patient population. The virus was examined for RAS by RNA sequencing before starting treatment. RAS mutations were determined through the cut-off value of RAS mutations that contributed in the successful therapy. All patients were followed up until 12 weeks after completion of treatment to determine the sustained virological response 12 (SVR12). Results: Out of the 58 patients, 9 patients (15.51%) did not achieve SVR. Only 14 patients was further analyzed to provide the association between the mutation and SVR-12 failure after sofosbuvir-daclatasvir therapy. Specifically, 2 patients with L31 mutation and one patient with L31/Y93 mutation achieved SVR. Only one patient with failure to achieve SVR and the mutation was found in Y93H region. Conclusion: The mutation of Y93H may contribute to treatment failure while L31A may increase the susceptibility to DAAs treatment.